Minimizing the maximum sender interference by deploying additional nodes in a wireless sensor network - Pushparaj Shetty D.; M. Prasanna Lakshmi (Electronic Journal of Graph Theory and Applications (EJGTA), 2019)
Interference is one of the major challenges faced by the communication networks. Since the interference leads to packet loss, packet collision and data re-transmission, higher the interference, higher is the energy consumption. Several algorithms were proposed for reducing the interference in a Wireless sensor network (WSN). By deploying additional nodes at an appropriate position in a WSN, it is possible to reduce the interference. We propose an algorithm in which, the main objective is to reduce the maximum Sender interference by deploying the additional nodes in the network, while connectivity of the network is preserved. We use the properties of Gabriel graph to achieve the reduction in interference. We present the simulation results which show the number of additional nodes to be deployed. The comparison of the maximum Sender interference obtained by the proposed algorithm with that of the Euclidean minimum spanning tree (MST) of the given network is presented through simulation. We show that the additional number of nodes required for deployment has an upper bound of n/2, where n is the number of nodes. We also compute the average reduction in Sender interference of the network for a various number of nodes.